Phytochemical constituents, a-glucosidase inhibitory activity and preliminary acute toxicity studies of the ethanol-water extracts of Salacca zalacca fruits in rats - Saleh, Mohammed S M; Siddiqui, Mohammad Jamshed Ahmad; Khatib, Alfi; Mat So'ad, Siti Zaiton (2018)
Purpose: To evaluate the phytochemical constituent screening, α-glucosidase inhibitory activity and in vivo preliminary toxicity study of ethanol and water S. zalacca fruit extracts. Methods: The fresh fruit was collected, cleaned, peeled, and dried using freeze dryer. The flesh powder was extracted using solvent with different concentration of ethanol and water (100, 80, 60, 40, 20, 0%). All extracts were tested for α-glucosidase inhibitory activity and phytochemical constituents were evaluated using different chemical methods. The extract showing highest α-glucosidase inhibitory activity was tested for acute toxicity studies according to the up and down method. A dose (0.15, 0.48, 1.54, 4.91 and 5.00 g/ kg body weight) of the extract was used in 15 healthy male rats. The rats were observed for 4 h first day, then daily for 14 days.